Manajemen Budaya Organisasi Multikultural di Perusahaan Indonesia Empiris - Ahmad Jet Alamin A; Margono; Heni A. Adilan (Jurnal Pariwisata Tawangmangu, 2025)
This study aims to examine the management of multicultural organizational culture in empirically based Indonesian companies. The research background is driven by the organizational need to manage cultural differences effectively so as to create a harmonious, productive, and adaptive workplace environment. The research method employs a quantitative approach, with data collection conducted through questionnaires administered to relevant stakeholders within the companies. The collected data were then analyzed using appropriate statistical techniques, including tools such as SPSS, as well as modeling and relationship analysis among variables using SEM. The results indicate that implementing multicultural organizational culture management contributes significantly to strengthening key organizational aspects, as reflected in the observed empirical data. The discussion further suggests that proper cultural management can enhance organizational effectiveness in responding to diversity. In conclusion, the study addresses the proposed hypotheses and provides recommendations for improving multicultural management practices, as well as suggestions for future research.